DEVELOPING ENGLISH SPEAKING MATERIAL THROUGH CBI FOR MARKETING STUDENTS ON VOCATIONAL HIGH SCHOOL - Dian . Lestari; Rahmad . Husein; Eddy . Setia (LINGUISTIK TERAPAN, 2021)
The Purpose of this study are; 1) to examine the existing English speaking materials of Marketing students; 2) to investigate English Speaking material which needed to meet with the marketing students’ need; 3) to develop English Speaking materials for Marketing students based on Content Based Instruction. . This study is descriptive qualitative research. This study inspired of ten stage of Educational Research and Development model by Gall, Gall and Borg, 2003. but in implementing the model is simplified and adapted to Dirgayasa (2011) become four steps: 1) Evaluation and need analysis, 2) designing new material, 3) validating material, 4) revision and final production. The instrument of collecting data was collected by questionnaire, documentation and interview. The source of the data was students of XI Marketing academic year 2018/2019, Marketing teacher, stake holder, alumnus and also syllabus and the existing speaking material used at this time. The result of  this study showed that 86 % students agree that they really need the relevant material which proper to their program and the analysis of the existing speaking materials and the existing syllabus showed that both are less relevant for English speaking skill for Marketing students. From the evaluation research got that learning method which used in the learning process found that it was less relevant. From evaluation research of documentation and interview agreed that the developing of speaking material for Marketing students is needed through Content Based Instruction. The final product of this speaking materials entitled English speaking materials for marketing. There are four topics in the book and it completed with teacher guide book.Keywords: Developing Speaking Material, Content Based Instruction, Marketing Students, Educational Research and Development